Differential Effect of Contrast Polarity Reversals in Closed Squares and Open L-Junctions - Schira, Mark M.; Spehar, Branka (Frontiers in Psychology, 2011)
Scene segmentation depends on interaction between geometrical and photometric factors. It has been shown that reversals in contrast polarity at points of highest orientation discontinuity along closed contours significantly impair shape discrimination performance, while changes in contrast polarity at straight(er) contour segments do not have such deleterious effects (Spehar 2002). Here we employ (semi) high resolution fMRI (1.5x1.5x1.5mm) to investigate the neuronal substrate underlying these perception effects. Stimuli consisted of simple elements a) squares with contrast reversals along straight segments; b) squares with contrast reversals in the corner (highest orientation discontinuity); c) L-Junctions with contrast reversals along the straight ends; d) L-Junctions with contrast reversals in the corner. Element with contrast polarity reversals are easy to distinguish though appear geometrically equivalent. For squares with contrast polarity reversals only along straight lines we find significantly lower BOLD modulation compared to any of the control conditions, which show similar responses to each other. In the light of previous psychophysical work (Spehar 2002, Elder and Zucker, 1993) we speculate that this effect is due to closure perception. We observe this across a wide range of areas on occipital cortex.